High‐dose corticosteroid use and risk of hospitalization for infection in patients treated with immune checkpoint inhibitors––A nationwide register‐based cohort study. (8th June 2021) - Sørup, Signe; Darvalics, Bianka; Russo, Leo; Oksen, Dina; Lamy, Francois‐Xavier; Verpillat, Patrice; AA, Khalil; HT, Sørensen; Cronin‐Fenton, Deirdre
Abstract: High‐dose corticosteroids have been associated with increased risk of serious infection in patients with metastatic melanoma treated with immune checkpoint inhibitors targeting cytotoxic T‐lymphocyte antigen 4. This potential association needs to be examined further among patients with other cancer types and for other immune checkpoint inhibitors. We examined whether receipt of high‐dose corticosteroids was associated with increased rates of hospitalization for infection among 981 Danish renal, urothelial, and lung cancer patients followed from first administration of programmed death receptor 1 (PD‐1)/programmed death ligand 1 (PD‐L1) immune checkpoint inhibitors. Our cohort analysis was based on the information from national medical registries. During follow‐up, 522 patients (53.2%) initiated treatment with high‐dose corticosteroids and 317 patients (32.3%) experienced at least one hospitalization for infection. In analyses adjusted for age, sex, and previous use of chemotherapy/targeted therapy, initiation of high‐dose systemic corticosteroids was associated with increased rate of hospitalization for infections (hazard ratio (HR) = 2.96, 95% confidence interval (CI) = 2.41–3.65) even in patients not receiving any chemotherapy/targeted therapy (HR = 3.66, 95% CI = 2.25–5.96). Our findings showed that high‐dose corticosteroid initiation is associated with hospitalization for infection in patients treated with PD‐1/PD‐L1 immune checkpoint inhibitors. Clinicians and patients should be aware of this risk of infection when initiating treatment with high‐dose corticosteroids. Abstract : High‐dose corticosteroids have been associated with increased risk of serious infection in metastatic melanoma patients treated with immune checkpoint inhibitors (ICIs) targeting cytotoxic T‐lymphocyte antigen 4. The present study adds that use of high‐dose corticosteroids is also associated with increased rate of hospitalization for infection among lung, kidney, and urothelial cancer patients treated with ICIs targeting programmed death receptor 1 or programmed death ligand 1 even in patients who did not receive chemotherapy/targeted therapy.